MENTORING SCHOOL PRINCIPALS AND TEACHERS IN INTERNALIZING THEOLOGICAL AND ETHICAL VALUES TO DEVELOP A CHARACTER-BASED SCHOOL CULTURE - Sukma Muharromi, Dewi; Patoni, Patoni; Nurjanah, Cucu; Rosmaladewi, Okke (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
ABSTRACT Schools are ideally designed as safe and dignified spaces that support students’ holistic development. However, in practice, bullying and juvenile delinquency remain prevalent issues that disrupt school climates. This condition is also evident in Plered District, particularly at SMP Negeri Satu Atap Rawasari, which faces challenges in internalizing moral and ethical values, in contrast to the relatively more conducive environment of SMP Negeri 1 Plered. This community service program aimed to strengthen the capacity of school principals and teachers to build a safe and character-based school culture through the reinforcement of theological and ethical values. The program employed a combined approach consisting of training, continuing education, awareness-raising, and participatory, context-based mentoring. The results indicate an increased level of understanding and awareness among principals and teachers regarding the role of theological and ethical values as foundational elements of leadership, school policies, and social relationships within educational settings. Participants began to perceive values not as supplementary programs but as an integral framework guiding school management and instructional practices. The program outcomes include shared commitments and improved readiness to implement religious and ethical value habituation in a more humanistic and sustainable manner. Overall, the program provides a significant initial contribution to strengthening character-based school culture and fostering a safe, humane, and dignified educational environment.